2009
DOI: 10.7547/0990512
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heel Height on Gait and Posture

Abstract: This article explores relevant full-text literature to reveal the effects of heel height on gait and posture and the kinetics and kinematics of the foot, ankle, knee, hip, and spine. Furthermore, special attention will be given to the implications of increased heel height for clinicians treating locomotor disorders and provide information to aid clinical decision making. Full-text articles accessed from databases including AMED, ASSIA, Blackwell Synergy, BNI, Voyager, CINAHL, ScienceDirect, and Taylor Francis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 50 publications
2
46
0
3
Order By: Relevance
“…Some studies [10][11][12] have shown that high-heeled shoes increase lumbar lordosis (LL) and change the relative orientation of the skeletal structures of the spine, which may increase mechanical loads and potentially promote discomfort and degenerative changes in the soft tissue [11]. However, contrary to the results of increased LL, other studies [13,14] have reported that experienced high-heeled shoe wearers show a reduction in LL.…”
Section: Introductionmentioning
confidence: 44%
“…Some studies [10][11][12] have shown that high-heeled shoes increase lumbar lordosis (LL) and change the relative orientation of the skeletal structures of the spine, which may increase mechanical loads and potentially promote discomfort and degenerative changes in the soft tissue [11]. However, contrary to the results of increased LL, other studies [13,14] have reported that experienced high-heeled shoe wearers show a reduction in LL.…”
Section: Introductionmentioning
confidence: 44%
“…[1][2][3][18][19][20] Searches of MANTIS, CINAHL, and Scopus found no additional original research; but the search of Scopus did reveal another, recent review of some effects of high-heeled shoes, 21 written for podiatrists and with only a small overlap with this present review. Two additional publications were found by happenstance in the Internet search for information available to the general public.…”
Section: The Peer-reviewed Literaturementioning
confidence: 99%
“…30,31 And no information has been provided about the spine during walking, nor of the effects of heels on hip, knee, or ankle joint positions or movements, nor on foot pathology related to altered pressures in the feet, changes in trunk and lower extremity muscle activity, or overall energy metabolism. Many of these topics have been reviewed by Cowley et al 21 ; and there is a plethora of other, original sources for the interested reader.…”
Section: Limitationsmentioning
confidence: 99%
“…Contudo, a relação do sapato de salto alto com dores das costas, especialmente com a lombalgia, não parece ser motivo de conflito entre os diversos estudos. Em outras palavras, existe um consenso que o mesmo favorece o aparecimento de dor nas costas 2,9 , porém permanece controversa a razão deste fato, ou seja, se está relacionado com o aumento ou com a diminuição dos ângulos das curvaturas da coluna, com o deslocamento anterior do centro de massa ou com ambos.…”
Section: Introductionunclassified